Globular Adiponectin Inhibits Ethanol-Induced Reactive Oxygen Species Production through Modulation of NADPH Oxidase in Macrophages: Involvement of Liver Kinase B1/AMP-Activated Protein Kinase Pathway - Kim, Mi Jin (Mol Pharmacol, 2014)
Adiponectin, an adipokine predominantly secreted from adipocytes, has been shown to play protective roles against chronic alcohol consumption. Although excessive reactive oxygen species (ROS) production in macrophages is considered one of the critical events for ethanol-induced damage in various target tissues, the effect of adiponectin on ethanol-induced ROS production is not clearly understood. In the present study, we investigated the effect of globular adiponectin (gAcrp) on ethanol-induced ROS production and the potential mechanisms underlying these effects of gAcrp in macrophages. Here we demonstrated that gAcrp prevented ethanol-induced ROS production in both RAW 264.7 macrophages and primary murine peritoneal macrophages. Globular adiponectin also inhibited ethanol-induced activation of NADPH oxidase. In addition, gAcrp suppressed ethanol-induced increase in the expression of NADPH oxidase subunits, including Nox2 and p22(phox), via modulation of nuclear factor-κB pathway. Furthermore, pretreatment with compound C, a selective inhibitor of AMPK, or knockdown of AMPK by small interfering RNA restored suppression of ethanol-induced ROS production and Nox2 expression by gAcrp. Finally, we found that gAcrp treatment induced phosphorylation of liver kinase B1 (LKB1), an upstream signaling molecule mediating AMPK activation. Knockdown of LKB1 restored gAcrp-suppressed Nox2 expression, suggesting that LKB1/AMPK pathway plays a critical role in the suppression of ethanol-induced ROS production and activation of NADPH oxidase by gAcrp. Taken together, these results demonstrate that globular adiponectin prevents ethanol-induced ROS production, at least in part, via modulation of NADPH oxidase in macrophages. Further, LKB1/AMPK axis plays an important role in the suppression of ethanol-induced NADPH oxidase activation by gAcrp in macrophages.